Populism, protest and democracy in the twenty-first century - O'Brien, T (Taylor and Francis, 2016)
Protest is an important measure of discontent within society and can be seen as a form of politics by other means. In periods of uncertainty and instability, protest can harm incumbent regimes by heightening and amplifying tensions, potentially leading to crisis and collapse in extreme cases. The wave of democratisation that characterised the last quarter of the 20th century saw a number of weak democracies emerge and struggle, whereas other regime changes saw new forms of authoritarianism emerge. Crises in the early 21st century have shaken both democratic and non-democratic states, leading to large-scale ‘occupy’ movements and uprisings that have brought down regimes in the former Soviet Union and across the Middle East and North Africa (MENA)1 region. Common to these diverse protests is a feeling of anti-politics that draws on populist and religious motivations to challenge the state. The aim of this paper is to consider the significance of this apparent wave of protest and identify the driving factors. In order to do this the paper examines arguments around the quality of democracy (and autocracy), state-social movement interactions and the rise of populist and religious movements.